Analisis Tren dan Volatilitas Saham BBRI Menggunakan Moving Average dan Standar Deviasi - Andreas Doloksaribu (SOTVI - Society of Visual Informatics, 2025)
Bank Rakyat Indonesia (BBRI) is one of the largest banks in Indonesia with significant market capitalization. This study aims to analyze price trend movements and stock volatility of BBRI for the period of January 2023 - October 2025 using Simple Moving Average (SMA) 20 and 50 days and Standard Deviation 20 days. Daily data (672 observations) were analyzed to identify trend patterns and investment risk levels. The results show that BBRI stock experienced a strong uptrend phase in 2023 (+33.1%), followed by a rally to a peak of IDR 5,763 in May 2024. However, the mid-2024 period was marked by high volatility with a whipsaw pattern (false signals), where the October 2024 Death Cross confirmed a final decline to the lowest level of IDR 3,176 (-44.9% from the peak). Volatility varied from 40 IDR (lowest, July-August 2023) to 425 IDR (highest, May-June 2024), indicating a negative correlation with trend strength. Moving Average is effective in identifying major trend changes, providing practical implications for technical analysis-based investment strategies.